Penerapan Algoritma K-Means Dalam Pengelompokan Kesejahteraan Rakyat Berdasarkan Kecamatan di Kabupaten Karawang - Dinda Fitriani; Tesa Nur Padilah; Betha Nurina Sari (STMIK Banjarbaru, 2021)
AbstrackTo make it easier for the government to implement policies related to people's welfare issues, it is necessary to know which areas have low levels of people's welfare, so that the government can prioritize the welfare of the people in that region. In this regard, it is necessary to classify the welfare of the people based on the existing area. This paper applies data mining techniques with the k-means algorithm in classifying people's welfare based on sub-district areas. The results of data processing with the help of tools Rstudio 4.0.5 obtained 3 clusters. Cluster 1 is a cluster with a high level of people's welfare, consisting of 7 sub-districts. Cluster 2 is a cluster with a moderate level of people's welfare, consisting of 8 sub-districts. Cluster 3 is a cluster with a low level of people's welfare, consisting of 7 sub-districts. In clustering with 3 clusters, the SSE value is 23,58788, and the accuracy rate is 72.9%.Keywords: People's Welfare, Data Mining, K-Means Clustering AbstrakUntuk mempermudah pemerintah mengimplementasikan kebijakan yang terkait dengan masalah kesejahteraan rakyat, perlu diketahui daerah mana saja yang memiliki tingkat kesejahteraan rakyat rendah, sehingga pemerintah dapat memprioritaskan kesejahteraan rakyat pada wilayah tersebut. Berkaitan dengan hal tersebut, perlu dilakukan pengelompokkan kesejahteraan rakyat berdasarkan wilayah yang ada. Paper ini menerapkan teknik data mining dengan algoritma k-means dalam pengelompokan kesejahteraan rakyat berdasarkan wilayah kecamatan. Hasil pengolahan data dengan bantuan tools Rstudio 4.0.5 diperoleh 3 cluster. Cluster 1 merupakan cluster dengan tingkat kesejahteraan rakyat tinggi, terdiri dari 7 kecamatan. Cluster 2 merupakan cluster dengan tingkat kesejahteraan rakyat sedang, terdiri dari 8 kecamatan. Cluster 3 merupakan cluster dengan tingkat kesejahteraan rakyat rendah, terdiri dari 7 kecamatan. Dalam melakukan clustering dengan 3 cluster diperoleh nilai SSE sebesar 23.58788, dan tingkat akurasi sebesar 72.9%.Kata kunci: Kesejahteraan Rakyat, Data Mining, K-Means Clustering